Identification of Group `E' Chromosome Abnormalities in Human Cells - Vause, Katharine E. (1973)
The specific adenovirus type-12 induced aberration in chromosome No. 17 has been used to identify this autosome in cells from patients with No. 17/18 (E group) chromosome abnormalities. The results show that all the cases examined involved abnormalities of chromosome No. 18.